Chapter Retirement as going through a portal of possibilities - Lykke, Nina (Amsterdam University Press, 2023)
The essay contemplates retirement as a portal of possibilities which may open time for diving into both haunting and joyful questions that being tied up with admin work formerly prevented the pursuit of. Questions which the retired academic could engage in are piled up, e.g. the haunting ones concerning classical humanities' celebration of Universal (White) Man and human exceptionalism. Questions about portals leading from the haunted space of the Humanities to an elsewhere, and what to take with us through these portals, are also addressed. Critique and aesthetics are discussed as possibly worthwhile to carry to the other side.